2008
DOI: 10.1073/pnas.0804699105
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and cellular signatures of human vaccine adjuvants

Abstract: Oil-in-water emulsions are potent human adjuvants used for effective pandemic influenza vaccines; however, their mechanism of action is still unknown. By combining microarray and immunofluorescence analysis, we monitored the effects of the adjuvants MF59 oil-in-water emulsion, CpG, and alum in the mouse muscle. MF59 induced a time-dependent change in the expression of 891 genes, whereas CpG and alum regulated 387 and 312 genes, respectively. All adjuvants modulated a common set of 168 genes and promoted antige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

24
335
2
12

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 440 publications
(380 citation statements)
references
References 29 publications
(47 reference statements)
24
335
2
12
Order By: Relevance
“…Both PT and CpG promote maturation of DCs, induce them to produce cytokines including IL-12 and IFN-γ, and enhance Ag presentation (14,17,19,32). The mechanism by which NE enhances immunogenicity is not completely understood, but available data suggest that MF59 triggers a local inflammatory environment by engaging muscle cells at the injection site, which then indirectly activates DCs (20). Regardless of the direct effect on DCs, activation of DCs could shift Ag presentation away from memory B cell to DCs, resulting in more recruitment of FM1-specific naïve B cells into the response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both PT and CpG promote maturation of DCs, induce them to produce cytokines including IL-12 and IFN-γ, and enhance Ag presentation (14,17,19,32). The mechanism by which NE enhances immunogenicity is not completely understood, but available data suggest that MF59 triggers a local inflammatory environment by engaging muscle cells at the injection site, which then indirectly activates DCs (20). Regardless of the direct effect on DCs, activation of DCs could shift Ag presentation away from memory B cell to DCs, resulting in more recruitment of FM1-specific naïve B cells into the response.…”
Section: Discussionmentioning
confidence: 99%
“…So far, two NE adjuvants, MF59 and AS03, have been approved for human use in Europe but not in the United States. Although the exact mechanisms of the action remain unclear, studies show that NE similarly enhances innate immunity by recruiting DCs to the site of injection and by promoting cytokine production (20,21). Several clinical studies have shown that NE enhances immunogenicity of inactivated influenza vaccines while being well tolerated by recipients (22)(23)(24)(25).…”
mentioning
confidence: 99%
“…Data from our laboratory may help address this issue. By performing microarray analysis of mouse muscle following adjuvant administration, we have found that alum injection results in the transcriptional up-regulation of several proinflammatory cytokines including IL-1b through a still unidenti- fied mechanism [24]. Recently it was shown that the aluminduced proliferation of antigen-specific T cells in draining lymph nodes depends on the local production of uric acid, a known activator of Nlrp3 [14].…”
Section: Is the Inflammasome Required For Alum Adjuvanticity?mentioning
confidence: 99%
“…Mosca et al demonstrated that MF59 together with CpG and alum activated innate immunity at the site of injection [17]. Using microarray analysis, the early genes induced in gluteus muscle of mice was examined by different adjuvant formulations.…”
mentioning
confidence: 99%
“…The cluster of genes modulated by all adjuvants, named 'adjuvant core response genes', were characterised by the upregulation of cytokines (IL-1 and IL-2), chemokines (such as CCL2, CCL12 and CXCL10) and adhesion molecules, suggesting the establishment of an immunocompetent environment at the site of injection [17].…”
mentioning
confidence: 99%